Digital Color Image Watermarking Using Encoded Frequent Mark (Journal of Engineering, 2019)
With the increased development in digital media and communication, the need for methods to protection and security became very important factor, where the exchange and transmit date over communication channel led to make effort to protect these data from unauthentication access.This paper present a new method to protect color image from unauthentication access using watermarking. The watermarking algorithm hide the encoded mark image in frequency domain using Discrete Cosine Transform. The main principle of the algorithm is encode frequent mark in cover color image. The watermark image bits are spread by repeat the mark and arrange in encoded method that provide algorithm more robustness and security. The proposed algorithm efficiency is measured by using many of measurement factors such as Peak Signal to Noise Ratio PSNR and Normalized Correlation Coefficient NC, the watermark robustness and feasibility are measured by using many types of attacks.